Pemetaan Status Kerusakan Tanah Lahan Pertanian di Kecamatan Selo, Kabupaten Boyolali - Kholishotu Syahidah; Sumarno Sumarno; Sri Hartati (Agrosains : Jurnal Penelitian Agronomi, 2016)
Intensively land use for biomass production without applying sustainable and sustained plant farming technique in District Selo potentially causes soil damage. Determination of soil potential damage and soil damage status has been set by the central government through Government Regulation No. 150 year 2000 on Soil Damage Control for Biomass Production. The research method used was a descriptive survey with a stage-setting soil potential damage by overlay thematic maps and the determination of the status of soil damage using matching methods and relative frequency score. Results obtained in the land area of the District Selo potentially medium damage 1,439.3 hectares and 1,988.8 hectares of high potential damage. After survey and laboratory analysis of soil samples at the site results that the Status of Soil Damage categorized light (R.I) with a score relative frequency of each 8. Total area that included minor damage divided into 3,296.97 hectares with limiting factors texture and permeability and 59.32 hectares with limiting factors permeability.